STABILITAS DAN VISKOSITAS PRODUK EMULSI Virgin Coconut Oil-MADU [The Stability and Viscosity of Virgin Coconut Oil-Honey Emulsion] - Feti Fatimah; Johnly Rorong; Sanusi Gugule (Jurnal Teknologi dan Industri Pangan, 2012)
This study was conducted to develop an alternative energy drink from VCO and honey. The objective of the study was to find out the relationship between VCO and honey concentration, viscosity and emulsion stability. The viscosity was measured by viscometer and the diameter of emulsion droplet was measured from microscopic images. The results showed that the increases of VCO and honey concentration corresponds to the increase of viscosity, and the reduction of emulsion droplet diameter sizes. From the viscosity and emulsion stability parameters, it could be concluded that the best formulation VCO-honey emulsion drink should contain 25-35% of VCO and 20-25% of honey. The emulsion products of VCO-honey at 25-35% of VCO had viscosity of 21-27 poise and the products at 20-25% of honey had viscosity of 14-21 poise. The stable emulsion product of VCO-honey had the emulsion droplet diameter of 2-5 µm.